Association of Vitamin D with Biochemical Severity Markers in Dengue Patients - Adnan Ghafoor, Mohammed Rehan Omar Siddiqi, Ali Ghazanfar, Maria Sarfraz, Aleena Hamid Shah, Fatima Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue fever is a common virus that has rapidly spread to all parts of the world. Dengue causes two critical disease dengue shock syndrome and dengue hemorrhagic fever. Aim: To determine whether vitamin D levels and the severity of dengue are linked in any way. Study design: Cohort study Place and duration of study: Department of Medicine, Fauji Foundation Hospital Rawalpindi from 15-08-2022 to 15-11-2022. Methodology: The patient's sample was collected to monitor the complete blood picture, including total leukocyte count and hemoglobin, hematocrit, platelets, etc. The severity of dengue was assessed by looking at platelet counts and hematocrit. Results: The mean age was 29.19±16.80 years. There were 51% females and 49% males in the study. Vitamin D levels and platelet levels were weakly correlated with each other (rs= -.408, p= .000). There was a strong, negative correlation between Hb and Vitamin D levels, which was statistically significant (rs= -.704, p= .000). Similarly, hematocrit and highest MCHC also had a strong inverse significant correlation with Vitamin D level (rs= .698, p = .000 and rs= .751, p= .000, respectively). Surprisingly, there were significantly higher vitamin D levels in severe dengue patients than in non-severe ones (p<0.01). Conclusion: Vitamin D levels were higher in severe dengue cases compared to less severe ones, indicating a possible role of vitamin D as a cofactor for predicting disease severity. It is suggested that maintaining an ideal vitamin D level can help avoid the progression of asymptomatic dengue to dengue hemorrhagic fever or dengue shock syndrome. Keywords: Vitamin D, Biochemical severity markers, Dengue